Dose-dependent decrease in anti-oxidant capacity of whole blood after irradiation: A novel potential marker for biodosimetry - Sun, Lue (Sci Rep, 2018)
Many reports have demonstrated that radiation stimulates reactive oxygen species (ROS) production by mitochondria for a few hours to a few days after irradiation. However, these studies were performed using cell lines, and there is a lack of information about redox homeostasis in irradiated animals and humans. Blood redox homeostasis reflects the body condition well and can be used as a diagnostic marker. However, most redox homeostasis studies have focused on plasma or serum, and the anti-oxidant capacity of whole blood has scarcely been investigated. Here, we report changes in the anti-oxidant capacity of whole blood after X-ray irradiation using C57BL/6 J mice. Whole-blood anti-oxidant capacity was measured by electron spin resonance (ESR) spin trapping using a novel spin-trapping agent, 2-diphenylphosphinoyl-2-methyl-3,4-dihydro-2H-pyrrole N-oxide (DPhPMPO). We found that whole-blood anti-oxidant capacity decreased in a dose-dependent manner (correlation factor, r > 0.9; P < 0.05) from 2 to 24 days after irradiation with 0.5–3 Gy. We further found that the red blood cell (RBC) glutathione level decreased and lipid peroxidation level increased in a dose-dependent manner from 2 to 6 days after irradiation. These findings suggest that blood redox state may be a useful biomarker for estimating exposure doses during nuclear and/or radiation accidents.